NIMG-63. ADVANCED IMAGING FOR ASSESSING VOLUMETRIC RESPONSES IN BRAIN METASTASES TREATED WITH CHECKPOINT BLOCKADE. (5th November 2018) - Gerstner, Elizabeth; Cardona, Jonathan; Chang, Ken; Beers, Andrew; Brown, James; Kalpathy-Cramer, Jayashree; Lee, Eudocia; Lin, Nancy; Tolaney, Sara; Nayak, Lakshmi; Chukwueke, Ugonma; Oh, Kevin; et al.
Abstract: BACKGROUND: Immunotherapy has been effective therapy for brain metastases (BM) from melanoma and lung cancer, prompting interest in using PD-1 targeting drugs in more patients with BM. However, accurately assessing response in patients undergoing immunotherapy continues to be a challenge. Thus, we prospectively evaluated radiographic characteristics and changes during immunotherapy. METHODS: As part of an ongoing Phase 2 study of pembrolizumab for patients with untreated or progressive, previously treated BM from any histology, patients underwent advanced MRI that includes tumor volume measurements and perfusion imaging with dynamic susceptibility contrast MRI.. To calculate volumetric radiographic response, all enhancing voxels were summated. A volumetric increase of >40% was categorized as progressive disease (PD), a decrease of >60% as partial response (PR), and stable disease (SD) as between -60% and +40%. RESULTS: Forty-eight patients have been enrolled of whom 38 have undergone at least baseline advanced MR imaging. Histologies include 16 with breast cancer (12 HER2-, 4 HER2+), 5 with non-small cell lung cancer, 4 with melanoma, and 11 with other cancers. At baseline, the total number of BM was 1–50+ per patient. Based on summing the entire enhancing intracranial disease burden, best volumetric responses for the 25 evaluable patients include 2 PR, 9 SD, and 14 PD. Cerebral blood volume tended to increase with increasing tumor size. Correlation of volumetric response to patient outcome and standardized response criteria (iRANO) is ongoing. CONCLUSIONS: Pembrolizumab may have activity in metastatic brain cancer. Ongoing analyses are evaluating if physiological MRI can shed light on the biological impact of pembrolizumab and response mechanisms in this patient population.